Electrospun nanofibers: A nanotechnological approach for drug delivery and dissolution optimization in poorly water-soluble drugs - Luis Castillo-Henríquez; Rolando Vargas-Zúñiga; Jorge Pacheco-Molina; Jose Vega-Baudrit (International Association of Physical Chemists (IAPC), 2020)
Electrospinning is a novel and sophisticated technique for the production of nanofibers with high surface area, extreme porous structure, small pore size, and surface morphologies that make them suitable for biomedical and bioengineering applications, which can provide solutions to current drug delivery issues of poorly water-soluble drugs. Electrospun nanofibers can be obtained through different methods asides from the conventional one, such as coaxial, multi-jet, side by side, emulsion, and melt electrospinning. In general, the application of an electric potential to a polymer solution causes a charged liquid jet that moves downfield to an oppositely charged collector, where the nanofibers are deposited. Plenty of polymers that differ in their origin, degradation character and water affinity are used during the process. Physicochemical properties of the drug, polymer(s), and solvent systems need to be addressed to guarantee successful manufacturing. Therefore, this review summarizes the recent progress in electrospun nanofibers for their use as a nanotechnological tool for dissolution optimization and drug delivery systems for poorly water-soluble drugs.